String phenomenology : (World Scientific, 2004)
This book contains a remarkable overview of the current trends in string phenomenology, through the contributions of an international team of researchers who present their latest results. Dedicated to the memory of the late Professor Ian Kogan, this volume will fill a gap in the literature on a comprehensive overview of the subject.